PENGARUH KONFLIK KERJA, KOMUNIKASI DAN STRESS KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN ACEH UTARA - Adi Dharma; Aiyub Aiyub; Ibrahim Qamarius (Universitas Malikussaleh, 2022)
This study aims to (1) determine the effect of work conflict, communication and job stress on job satisfaction. (2) knowing work conflict, communication, job stress and job satisfaction on employee performance (3) knowing job satisfaction mediating the relationship between work conflict, communication and job stress on employee performance. The data used in this study is primary data as many as 139 respondents at the North District Education and Culture Office. The data analysis method in this study uses a structural equation model with the help of an analysis of moment structure. The results of the study found that work conflict and communication had a positive and significant effect on job satisfaction, while job stress had no effect on job satisfaction. Furthermore, communication and job satisfaction have a positive and significant effect on employee performance, while work stress has a negative and significant effect on employee performance, but work conflict has no effect on employee performance. Job satisfaction is able to mediate the relationship between work conflict and job satisfaction partially mediation, while job satisfaction is able to mediate the relationship between communication and job satisfaction in full mediation and job satisfaction is not able to mediate the relationship between job stress and job satisfaction